Morphological and Spatial Heterogeneity of Microbial Communities in Pilot-Scale Autotrophic Integrated Fixed-Film Activated Sludge System Treating Coal to Ethylene Glycol Wastewater - Jia, Fangxu; Chen, Jiayi; Zhao, Xingcheng; Liu, Chenyu; Li, Yiran; Ma, Jinyuan; Yang, Anming; Yao, Hong (Frontiers in Microbiology, 2022)
The understanding of microbial compositions in different dimensions is essential to achieve the successful design and operation of the partial nitritation/anammox (PN/A) process. This study investigated the microbial communities of different sludge morphologies and spatial distribution in the one-stage PN/A process of treating real coal to ethylene glycol (CtEG) wastewater at a pilot-scale integrated fixed-film activated sludge (IFAS) reactor. The results showed that ammonia-oxidizing bacteria (AOB) was mainly distributed in flocs (13.56 ± 3.16%), whereas anammox bacteria (AnAOB) was dominated in the biofilms (17.88 ± 8.05%). Furthermore, the dominant AnAOB genus in biofilms among the first three chambers was Candidatus Brocadia (6.46 ± 2.14% to 11.82 ± 6.33%), whereas it was unexpectedly transformed to Candidatus Kuenenia (9.47 ± 1.70%) and Candidatus Anammoxoglobus (8.56 ± 4.69%) in the last chamber. This demonstrated that the niche differentiation resulting from morphological (dissolved oxygen) and spatial heterogeneity (gradient distribution of nutrients and toxins) was the main reason for dominant bacterial distribution. Overall, this study presents more comprehensive information on the heterogeneous distribution and transformation of communities in PN/A processes, providing a theoretical basis for targeted culture and selection of microbial communities in practical engineering.